Safety and immunogenicity of the tau vaccine AADvac1 in patients with Alzheimer's disease: a randomised, double-blind, placebo-controlled, phase 1 trial. Issue 2 (February 2017) - Novak, Petr; Schmidt, Reinhold; Kontsekova, Eva; Zilka, Norbert; Kovacech, Branislav; Skrabana, Rostislav; Vince-Kazmerova, Zuzana; Katina, Stanislav; Fialova, Lubica; Prcina, Michal; Parrak, Vojtech; Dal-Bianco, Peter; et al.
Summary: Background: Neurofibrillary pathology composed of tau protein is a main correlate of cognitive impairment in patients with Alzheimer's disease. Immunotherapy targeting pathological tau proteins is therefore a promising strategy for disease-modifying treatment of Alzheimer's disease. We have developed an active vaccine, AADvac1, against pathological tau proteins and assessed it in a phase 1 trial. Methods: We did a first-in-man, phase 1, 12 week, randomised, double-blind, placebo-controlled study of AADvac1 with a 12 week open-label extension in patients aged 50–85 years with mild-to-moderate Alzheimer's disease at four centres in Austria. We randomly assigned patients with a computer-generated sequence in a 4:1 ratio overall to receive AADvac1 or placebo. They received three subcutaneous doses of AADvac1 or placebo from masked vaccine kits at monthly intervals, and then entered the open-label phase, in which all patients were allocated to AADvac1 treatment and received another three doses at monthly intervals. Patients, carers, and all involved with the trial were masked to treatment allocation. The primary endpoint was all-cause treatment-emergent adverse events, with separate analyses for injection site reactions and other adverse events. We include all patients who received at least one dose of AADvac1 in the safety assessment. Patients who had a positive IgG titre against the tau peptide component of AADvac1 at least once during the study were classified as responders. The first-in-man study is registered with EU Clinical Trials Register, number EudraCT 2012-003916-29, andClinicalTrials.gov, numberNCT01850238 ; the follow-up study, which is ongoing, is registered with EU Clinical Trials Register, number EudraCT 2013-004499-36, andClinicalTrials.gov, numberNCT02031198 . Findings: This study was done between June 9, 2013, and March 26, 2015. 30 patients were randomly assigned in the double-blind phase: 24 patients to the AADvac1 group and six to the placebo group. A total of 30 patients received AADvac1. Two patients withdrew because of serious adverse events. The most common adverse events were injection site reactions after administration (reported in 16 [53%] vaccinated patients [92 individual events]). No cases of meningoencephalitis or vasogenic oedema occurred after administration. One patient with pre-existing microhaemorrhages had newly occurring microhaemorrhages. Of 30 patients given AADvac1, 29 developed an IgG immune response. A geometric mean IgG antibody titre of 1:31415 was achieved. Baseline values of CD3+ CD4+ lymphocytes correlated with achieved antibody titres. Interpretation: AADvac1 had a favourable safety profile and excellent immunogenicity in this first-in-man study. Further trials are needed to corroborate the safety assessment and to establish proof of clinical efficacy of AADvac1. Funding: AXON Neuroscience SE.